2005
DOI: 10.1021/la046851s
|View full text |Cite
|
Sign up to set email alerts
|

A Mild Photoactivated Hydrophilic/Hydrophobic Switch

Abstract: Surface modification using light is one of the most powerful methods for controlling the physical and chemical properties offunctionalized surfaces. In this paper, we report on systems where soft UV irradiation (lambda = 365 nm) converts a "low" activity fluorocarbon to a "high" activity amine-functionalized surface. An amine-functionalized SAM (self-assembled monolayer) is first masked using a tertiary amine catalyzed reaction with an N-hydroxysuccinimidyl carbonyl reagent. This mild, room-temperature reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(87 citation statements)
references
References 62 publications
3
84
0
Order By: Relevance
“…3,4 Although most workers have concentrated on the photochemistry of ortho nitrobenzyl derivatives, almost any preparative photochemical reaction can be adapted for use in the SAM environment. 5,6 However, preparative photochemical reactions that give high yields in dilute solution do not necessarily…”
Section: /0#and- %#/-0mentioning
confidence: 99%
“…3,4 Although most workers have concentrated on the photochemistry of ortho nitrobenzyl derivatives, almost any preparative photochemical reaction can be adapted for use in the SAM environment. 5,6 However, preparative photochemical reactions that give high yields in dilute solution do not necessarily…”
Section: /0#and- %#/-0mentioning
confidence: 99%
“…SAMs that are designed to photo-deprotect under soft UV light can be combined with simple alkanethiol SAMs (e.g., Octodecanethiol [44]) to produce new geometries not easily achieved using deep UV light or microcontact printing alone. Ryan et al [45] demonstrated that SAMs of methoxy-nitrobenzyl derivatives could be photopatterned to produce 'three-component' surface functionality.…”
Section: Multi-component Patterningmentioning
confidence: 99%
“…Several researchers have demonstrated that photopatterning can be achieved using soft UV ( ÂŒ 365 nm, h $ 3.4 eV) light by incorporating photo-reactive orthonitrobenzyl chromophores [42][43][44][45][46][47][48][49][50][51][52][53][54][55]. At this wavelength, the photon energy is not sufficient to cause any significant photo-oxidisation of the SAM headgroups, and so we rely upon photochemistry to cleave the molecules at a designated bond to reveal new functionality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The use of soft UV (365 nm) photolithography of ortho-nitrobenzyl protected SAMs provides a potentially attractive alternative since this offers much greater control over the chemical functionality of the surface. [32][33][34] Recently, we have shown that it is possible to obtain photolysis yields of ~ 95%…”
Section: Introductionmentioning
confidence: 99%